Penerapan Sistem Kendali PID pada Antena Pendeteksi Koordinat Posisi UAV - Mahendra Budi Nugraha; Raden Sumiharto (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2015)
In this project has been implemented a PID control system on antenna tracker of unmanned aerial vehicle coordinates. PID control system on antena tracker to be used on horizontal and vertikal motion control. The setpoint of PID controller for horizontal motion is azimuth’s angle between antenna and UAV. The angle produced by azimuth’s method between two coordinates. The setpoint of PID controller for vertical motion is elevasi’s angle that produced by haversine-formula’s method and Sinus Trigonometry between distance two coordinates toward altitude of UAV. Tuning of PID controller was calculated by Ziegler-Nichols’s method with oscillation’s method and reasoning table of Ziegler-Nichols.The result from this project is implementation PID control system with Ziegler-Nichols’s method. There ara 3 variations in Ziegler-Nichols’s table, that are P, PI, and PID control system. The PD control system also implemented with integral’s control set on 0. The control system that has a good response is PD control system with Kp = 11,375 and Kd = 0,372531 on azimuth’s control whereas elevasi’s control with Kp = 3,41 and Kd = 0,111464. Response that produced by azimuth’s control is 0,32 second and elevasi’s control is 0,34 second.